Harvard Catalyst | The Clinical Translational Science Center IND/IDE Consult Service: Providing an IND/IDE Consult Service in a Decentralized Network of Academic Healthcare Centers - Min J. Kim; Sabune J. Winkler; Barbara E. Bierer; Delia Wolf (Wiley, 2014)
Abstract The Food and Drug Administration (FDA) regulations require sponsors of clinical investigations involving an investigational drug or device to submit an Investigational New Drug (IND) or Investigational Device Exemption (IDE) application. Strict adherence to applicable regulations is vital to the success of clinical research. Unlike most major pharmaceutical sponsors, investigator sponsors often do not fully appreciate their regulatory obligations nor have resources to ensure compliance. As a result they can place themselves and their institutions at risk. Nevertheless, investigator‐initiated clinical trials are vital to the further development of innovative drugs, biologics, and medical devices. The IND/IDE Subcommittee under the Regulatory Knowledge and Support Program at Harvard Catalyst, The Harvard Clinical and Translational Science Center worked in collaboration with Harvard and Harvard affiliated institutions to create and launch an IND/IDE Consult Service in a decentralized network of collaborating Academic Healthcare Centers (AHC). The IND/IDE Consult Service offers expertise, resources, and shared experiences to assist sponsor‐investigators and IRBs in meeting regulatory requirements for conducting and reviewing investigator‐initiated IND/IDE studies. The scope of the services provided by the Harvard Catalyst IND/IDE Consult Service are described, including the specifics of the service, lessons learned, and challenges faced, in a scalable model that builds inter‐institutional capacity.